2018
DOI: 10.1103/physrevb.97.155429
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of electronic and magnetic properties in the transition metal doped Sb2Te3 quantum anomalous Hall platform

Abstract: The quantum anomalous Hall effect (QAHE) has recently been reported to emerge in magnetically doped topological insulators. Although its general phenomenology is well established, the microscopic origin is far from being properly understood and controlled. Here, we report on a detailed and systematic investigation of transition metal (TM) doped Sb 2 Te 3. By combining density functional theory calculations with complementary experimental techniques, i.e., scanning tunneling microscopy, resonant photoemission, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 76 publications
3
47
0
Order By: Relevance
“…The observed Sb 5p magnetic moment at the non-magnetic element is most likely induced by the V magnetic dopant. This result is in good agreement with the previous XMCD studies for Cr-or V-doped compounds [29,33,35,36,38]. More importantly, very small but clear XMCD signals are observed at the Te M 4,5 absorption edges.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The observed Sb 5p magnetic moment at the non-magnetic element is most likely induced by the V magnetic dopant. This result is in good agreement with the previous XMCD studies for Cr-or V-doped compounds [29,33,35,36,38]. More importantly, very small but clear XMCD signals are observed at the Te M 4,5 absorption edges.…”
Section: Resultssupporting
confidence: 92%
“…The microscopic origin of the ferromagnetism and the QAH state has been extensively investigated by theoretical and experimental approaches [26][27][28][29][30][31][32][33][34][35][36][37][38]. Element-specific x-ray absorption spectroscopy (XAS) and x-ray magnetic circular dichroism (XMCD) experiments revealed that the long-range ferromagnetic order in the magnetic TIs is caused by a magnetic coupling between p-d electrons of the host and magnetic dopants because the clear XMCD signals were observed not only at V (Cr) sites but also at Sb sites [29,33,35,36,38]. In addition, first principles calculations, scanning tunneling microscopy/spectroscopy (STM/STS) and resonant photoemission spectroscopy identified the impurity states of vanadium dopants at or near the Dirac node [26,30,32,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, this large upward rescaling of the U-axis, as well as the non-infinite critical potential for changing the Dirac point connection topology ¹ ¥ ( ) U C , and the appearance of successive Dirac-connected states as a function of U, reveal that including 3D structure and coupling with bulk band symmetries can have an important role in defining the edge state properties. This finding is consistent with other recent literature suggesting that impurity state LDOS may include a significant bulk band component at a TI surface [14,26,39,40]. However, the rescaled 2D CL model can do an excellent job for edge states with group velocities not far removed from their band of origin (the lower or upper Dirac cone), and accurately describes the low-momentum dispersion for over half of the parameter space explored in figure 4(e).…”
Section: Physical Steps In a 3d Tight Binding Modelsupporting
confidence: 91%
“…We point out that the impurityinduced in-gap states are strongly localized in the vicinity of the impurities, so that at larger distances the magnetic proximity effect could still lead to a gap in density of states (of the surface state). This could support a quantum anomalous Hall state [31,47,48].…”
Section: Discussionmentioning
confidence: 73%